A flexible tool for calculating the consequences of a hypothetical nuclear accident - Eugenio Tabet (Istituto Superiore di Sanità, 2011)
The paper presents a parametric model, implemented on a personal computer, for calculating contamination and doses following a hypothetical nuclear accident. The model is embedded in the high level environment of Mathematica and uses the Gaussian solution for the plume structure at short and medium distances and a wedge-like behaviour for long distances calculation. Along with the usual effects, like the influence of a local wet ground deposition or the corrections due to build-up, the model deals also with other aspects, such as the long distance behaviour of the plume, by taking into account random wind direction variations. A rather sophisticated approach is used, in particular, when evaluating food contamination and doses, allowing also for consideration of a possible ban of food consumption. Several tens of functions are on hand of the user who can take full advantage of the very flexible tools introduced in the recent version 7 of Mathematica. Some examples of the power of the tool are shown with reference to the radiological consequences of an hypothetical accidental release in a EPR reactor.